PERANAN SEKTOR PERTANIAN TERHADAP PEREKONOMIAN DI KOTA BITUNG - Gustafito J.M. Wehantouw; Oktavianus ., Porajouw; Melissa L.G. Taroreh (AGRI-SOSIOEKONOMI, 2021)
The research aims to describe the role of the agricultural sector in the economy in Bitung City from 2010 to 2019. The study was conducted for 3 months from June 2020 to September 2020. The type of data used in this study is secondary data obtained from the Central Statistics Agency (BPS) of Bitung City, namely in the form of GRDP of Bitung City and North Sulawesi Province for the period 2010 to 2019. Supporting data is in the form of other secondary data relevant to this study. The data collected were analyzed descriptively and presented in tabular form. The results showed that the contribution of the agricultural sector to the GRDP of Bitung City in 2019 was 16.6 percent, although it has decreased since 2010 by 17.8 percent, but the agricultural sector still ranks second after the manufacturing sector with a contribution of 32.84 percent in in 2019. The growth of the agricultural sector, although fluctuating, tends to increase from 6.33 percent in 2012 to 9.06 percent in 2019. The LQ value of the agricultural sector, even though it was less than one in 2019, was 0.85, but continues to increase compared to last year. 2010 amounted to 0.75, and the agricultural sector, especially the capture or fishing fisheries sub-sector, is the exporting sector to other districts / cities in North Sulawesi Province. Based on the results of this study, it can be concluded that the agricultural sector has an important role in the economy of Bitung City, because this sector is not only an exporting sector, especially the capture fisheries sub-sector, but also as a provider of raw materials for the processing industry in Bitung City.